Paradox and existential method in the interpretation of Howard Slaatte - Shevchenko, Serhii (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2014)
The problem of the relation of existentialism and theology in the work of Howard Alexander is drain. Focused on the issue of inclusion of existentialist methodology in contemporary Christian theology, to study the concepts of “paradox”, “existential dialectic”, “myth-making”. Analyzes the work of Howard Slaatte, in which he reinterprets the theological positions of Kierkegaard, Berdyaev, P.Tillich, R.Bultman and other well-known representatives of the religious philosophy of existential direction, while proclaiming the need for a “balanced existential approach” to modernizing Christianity